If it's not what You are looking for type in the equation solver your own equation and let us solve it.
55x+3(9x+12)=-64
We simplify the equation to the form, which is simple to understand
55x+3(9x+12)=-64
Reorder the terms in parentheses
55x+(+27x+36)=-64
Remove unnecessary parentheses
+55x+27x+36=-64
We move all terms containing x to the left and all other terms to the right.
+55x+27x=-64-36
We simplify left and right side of the equation.
+82x=-100
We divide both sides of the equation by 82 to get x.
x=-1.21951219512
| 0=16t^2+128t+144 | | x+3.8=9.2 | | 4p+2p+6p-1= | | 7x-20=29 | | Ma-Th=fun | | -10x+10=-10 | | (4x^2)(-2x^3y^5)(-3xy)=0 | | 5x*5x= | | r(x)=-0.11x^2+100x | | 5n-18=-33 | | -5x+-30=80 | | 3(5z-3)-3(-2z)=6 | | 2(x-1)=3x-(x+2) | | 6s-15=-6+5a | | 9t-22=-29+8t | | -11x-31=-20 | | .5y+7=.75y-4 | | 32=(x-7)(x+7) | | 5(6c-4)+3(8c-1)= | | 2(3+5x)-5=31 | | 74-4x=14x+24 | | 15-2(w+5)=11 | | X+24=130 | | 11x-31=-20 | | x+9.8=14.5 | | 7=y-12 | | 3x-17=16-(2x+8) | | 2x+12=90+3x+23 | | 30x+3=123 | | 16x+420=-100 | | 7-2=13-3 | | 4(y+3)+7=4y+19 |